PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN CONSUMEN GOOD INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fakhriah, Ahda Fahira; Cahyaningtyas, Fadilla (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
The purpose of this study is to understand and analyze the effect of corporate social responsibility disclosure with earnings management, liquidity and profitability factors from companies in the consumer good industry sector for the period 2018-2020. In this study there were 20 company populations with a total of 60 samples as research objects. The method used in this research is multiple linear regression method. Related to this research, there is a conclusion that the results of the study indicate that there is a significant influence between earnings management, liquidity and profitability on the disclosure of corporate social responsibility. The implication of the results of this study is that companies can disclose the influence of corporate social responsibility if the company can meet the criteria of the GRI index, amounting to 91 criteria.